A Focus on Others and Commitment to Social Justice: A Social Cognitive Perspective. (May 2017) - Autin, Kelsey L.; Duffy, Ryan D.; Allan, Blake A.
As the importance of social justice advocacy is increasingly emphasized in vocational psychology, it is imperative for researchers to explore the development of individuals' interest in and commitment to social justice work. With a diverse sample of 298 undergraduate students, this study sought to replicate findings from Miller et al. which supported the use of social cognitive career theory in predicting social justice interest and commitment from social justice self-efficacy and outcome expectations. In addition, person inputs related to a focus on others were examined as predictors of social justice variables. Specifically, we explored whether collectivistic values and a calling orientation toward work predicted social justice outcomes. Results demonstrated replicability of Miller et al.'s model. Additionally, collectivism and sense of calling were each found to directly and indirectly predict social justice variables. Findings indicate that extent to which individuals endorse collectivism and a sense of calling may be useful in predicting how committed they are to social justice work.